Identitas Keacehan dalam Isu-Isu Syariatisasi, Kristenisasi, Aliran Sesat dan Hegemoni Barat - Al Makin (Islamica: Jurnal Studi Keislaman, 2016)
This article presents a study of the Acehnese religious identity in responding to the issues of shar??ah application in the province, Chirstian mission, deviant sects, and Western hegemony. These themes somehowe play a role in defining the Acehnese identity in the way in which the informants use these themes to project themselves; who they are in relating Islam to the Aceh identity. The spirit of conservatism can be seen in their feeling of being threatened by Christian missionary, deviant sects, and Western hegemo-ny. The application of shar??ah , on the other hand, gives another legitimacy of the Acehnese identity. Although the issue of shar??ah can be found in other provinces in Indonesia, shar??ah in Aceh is perceived to be different. This article also presents different voices of the Acehnese who are critical to their fellow Acehnese who support shar??ah appli-cation, and give negative reaction to the Christian mission, deviant sects and Western hegenomy. This article is based on a fieldwork by interviewing some informants in Banda Aceh in July 2013.